Residual de nutrientes no solo com fertilizante organomineral após cultivo de hortaliças - Torres, Dinamar Marcia da Silva Vieira Rodrigues (2019)
The use of organomineral fertilizer in the cultivation of vegetables improves the uniformity in concentration and availability of plant nutrients and with little losses. This slow release of nutrients ensures good supply to the plant during its whole cycle. The objective of this study was to evaluate the residual content of the application of different levels of fertilizers including phosphorus (P) via organomineral fertilizer in two soils and relate the results to the development of cabbage and lettuce crop. Two consecutive trials in pots, in different soils, with a randomized blocks design were installed. Five doses of organomineral as P source were applied in a dystrophic Red Latosol (LVd): T1 = 0; T2 = 50% (400 mg dm-3 of P2O5); T3 = 100% (800 mg dm-3 of P2O5); T4 = 200% (1600 mg dm-3 of P2O5) and T5 = 300% (2400 mg dm-3 of P2O5), plus an additional treatment (100% mineral). In the Melanic Gleysol (GM), T1 = 0; T2 = 50% (100 mg dm-3 of P2O5); T3 = 100% (200 mg dm-3 of P2O5); T4 = 200% (400 mg dm-3 of P2O5) and T5 = 300% (600 mg dm-3 of P2O5), plus an additional treatment (100% mineral) were applied. The production of fresh mass (FM) and dry matter (DM), the nutritional status of cabbage and lettuce by foliar analysis and the residual effect of nutrients in the soil after successive cultivations were evaluated. The F test for treatment significance was applied, and the averages were compared by the Tukey’s test (p < 0.05), and by Dunnet's test (p < 0.05) to compare the additional treatment to the other treatments. The residual level of the organomineral fertilizer was superior (p<0.05), as were the doses used in the LVd soil in both cycles evaluated; in GM soil, the same happened only in the first cycle (cabbage). Regardless of the type of soil the fertilization was essential to obtain significantly great FM and DM in vegetable crop production. The use of 50% of organomineral fertilizer dose in cabbage in both soils provided a production of FM and DM about 11% higher, when compared to the mineral fertilization. In lettuce, the greatest production occurred in the 100% mineral fertilization in the LVd, soil, while in the GM soil the greatest production occurred at 200% dose of organomineral fertilizer. The soil pH was significantly lower in soils with organomineral fertilizer, when compared to the soil that received only the mineral fertilization. The levels of P and K were significantly greater at a dose of 300% of organomineral fertilizer and 100% mineral fertilization (additional treatment), in both soils evaluated.